2016
DOI: 10.1097/md.0000000000004563
|View full text |Cite
|
Sign up to set email alerts
|

Significantly higher peripheral fibroblast growth factor-2 levels in patients with major depressive disorder

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
1
27
1
Order By: Relevance
“…It is especially suggestive that work from the Pritzker Neuropsychiatric Disorder Research Consortium allowed the important discovery that FGF, originally implicated in neural development, plays a crucial role in neurogenesis and in neuroplasticity in adulthood, suggesting a neuromodulatory function in anxiety-like and depression-like behaviors [47,48], providing support for our findings. In addition, altered levels of FGF family members were revealed in MDD patients, both in blood and in brain [49]. Altered levels of IGF-1, a neurotrophic, neurogenetic and neuroprotective factor, were repeatedly reported in MDD patients, although with conflicting results in the direction of change [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is especially suggestive that work from the Pritzker Neuropsychiatric Disorder Research Consortium allowed the important discovery that FGF, originally implicated in neural development, plays a crucial role in neurogenesis and in neuroplasticity in adulthood, suggesting a neuromodulatory function in anxiety-like and depression-like behaviors [47,48], providing support for our findings. In addition, altered levels of FGF family members were revealed in MDD patients, both in blood and in brain [49]. Altered levels of IGF-1, a neurotrophic, neurogenetic and neuroprotective factor, were repeatedly reported in MDD patients, although with conflicting results in the direction of change [46].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor-1 is an additional factor with neurogenic functions that may be increased in depression, reflecting an imbalance in neurotrophic processes 82,83. Basic fibroblast growth factor (or FGF-2) is a member of the fibroblast growth factor family and appears higher in depressed than control groups 84. However, reports are not consistent; one found that this protein was lower in MDD than healthy controls, but reduced further alongside antidepressant treatment 85…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on the role of neuronal regeneration in the pathogenesis and treatment for depression. According to the neurotrophic hypothesis of depression, brain derived neurotrophic factor (BDNF), tumor necrosis factor-α (TNF-α) ( 9 ), vascular endothelial growth factor (VEGF) ( 10 ) or fibroblast growth factor 2 (FGF-2) ( 11 ) may participate in the progression of depression.…”
Section: Introductionmentioning
confidence: 99%